HUTAN LESTARI AKANKAH RUSAK KARENA HPH? - Yunitasari, Duwi (Journal of Indonesian Applied Economics, 2008)
Forests are important resources for humans, since forests can provide added valueas well as the lungs of the world. forest management is faced with the HPH licenseHPH (Forest Management Right), which was often used as a means to earn a profitfor themselves. There is collusion in the form of license sales which gives benefit toboth  parties. Where  the  goverments  get  the money  as  the  benefit  while  theentrepreneurs get profit to exploit the forest and  the security guarantees  from  thegoverments.  In  here,  there  is  Patron-klien  pattern. Here  actually,  governmentintervention is needed as in the neo-classical theory. But, the fact the governmenthad  failed  to  intervene  because  of  the  limited  human  resources and  governmentadministration. So, it needs to strengthen the role of the moratorium Stake Holderand NGOs in the monitoring of forest management.Keywords: HPH, collusion, patron-client, government failure